New Age Movements, Occultism, and Spiritualism Research Library: The Making of a Pagan Archive - Frost, Guy (Pomegranate, 2018)
In 2016, a Pagan Archives was established in the Archives and Special Collections of Valdosta State University. Titled, the New Age Movements, Occultism, and Spiritualism Research Library (here forth called NAMOSRL), the drawing together of resources for this collection and from a variety of paths, faiths, and traditions was twelve years in the making. Individual archival contemporary Pagan and Wiccan source materials are few and far between but growing in number. Many of these archives devoted to contemporary Paganism or Wicca are private and tend to only acquire resources for a specific path. As the name suggests, NAMOSRL is designed as a research library. As such, the library contains books and periodicals, but also individual archival collections. The following narrative describes the development of this unique collection.